Integrasi Maqashid Syariah Dalam Strategi Manajemen Masjid Untuk Kemakmuran Dan Kesejahteraan Umat Studi Kasus Masjid Al-Amin Tanjung Buntung Batam - Safrizal, Safrizal; Amrizal, Amrizal; Safari, Arief; Yandri, Pitri; Budiasih, Yanti (Jurnal Sosial Teknologi, 2025)
Safrizal NIM 2361101026 The Integration of Maqashid Sharia in Mosque Management Strategy for the Prosperity and Welfare of the Ummah: A Case Study of Al-Amin Mosque, Tanjung Buntung, Batam This study aims to analyze the integration of Maqashid Syariah into mosque management strategies as an approach to improve community welfare and prosperity. A mosque is not only a place of worship but also a center for social and economic empowerment of Muslims. In this context, the Maqashid Syariah approach is essential as it reflects core Islamic values relevant to institutional governance. This study uses a qualitative approach with a case study method conducted at Al-Amin Mosque, Tanjung Buntung, Batam City. Data collection techniques include interviews, observations, and documentation, analyzed using the interactive model of Miles and Huberman. The results show that applying Maqashid Syariah principles in mosque management can strengthen institutional structures, increase congregation participation, and expand the mosque’s social impact on the surrounding community. This study is expected to contribute to the development of a Sharia-based mosque management model that is more relevant, applicable, and sustainable.